Arecanut-based cropping system fetches more return - Bhat, Ravi; Sujatha, S.; Chowdappa, P (Indian Horticulture, 2019)
Small and marginal holdings of less than one ha dominate in arecanut tract. Despite its commercial status, profitability is not assured for farmers due to recurrent problems like price fluctuations, pests and diseases, waterlogging and drought resulting in considerable yield losses. So, emphasis should be given to increase the productivity per unit area per unit time. The practice of well-planned and executed inter/mixed cropping is fundamental for increasing the productivity and income per unit area. Therefore, economically and environmentally-viable cropping models to empower small and marginal farmers are discussed.